Developing human resource in research and development: international experiences and implications for Vietnam. Issue 1 (2nd January 2020) - Tuan, Tran Minh; Dung, Nguyen Xuan
ABSTRACT: Human resource is the key driving force of research and development of a nation. Japan and Korea are two examples of how appropriate strategies in developing human resources have been transferred into remarkable achievements in R&D. In recent years, Vietnam has observed significant shift in investment for R&D. Thus, the lessons of Japan and Korea could provide Vietnam with valuable strategies for further development in human resources in R&D, particularly in vision of R&D development, policy flexibility, increased investment on R&D development and human resources, key R&D organization formation and increased international cooperation in S&T.